Perspectives of lipid metabolism reprogramming in head and neck squamous cell carcinoma: An overview - Miao, Xiangwan; Wang, Beilei; Chen, Kaili; Ding, Rui; Wu, Jichang; Pan, Yi; Ji, Peilin; Ye, Bin; Xiang, Mingliang (Frontiers in Oncology, 2022)
Recent studies showed that lipid metabolism reprogramming contributes to tumorigenicity and malignancy by interfering energy production, membrane formation, and signal transduction in cancers. HNSCCs are highly reliant on aerobic glycolysis and glutamine metabolism. However, the mechanisms underlying lipid metabolism reprogramming in HNSCCs remains obscure. The present review summarizes and discusses the “vital” cellular signaling roles of the lipid metabolism reprogramming in HNSCCs. We also address the differences between HNSCCs regions caused by anatomical heterogeneity. We enumerate these recent findings into our current understanding of lipid metabolism reprogramming in HNSCCs and introduce the new and exciting therapeutic implications of targeting the lipid metabolism.